Spatial Variations in Water Quality of Batang Ai Reservoir, Lubok Antu, Sarawak, Malaysia - Nurul Safinaz, binti Mohamad Kamal (Universiti Malaysia Sarawak, (UNIMAS), 2014)
In Sarawak, the Batang Ai Reservoir has been utilized for cage culture activities for many years since its impoundment in 1985. A few sites in the reservoir have been used for cage culture and one site has been abandoned. This study was carried out to document the water quality at three existing aquaculture sites, one abandoned site, and one station further from cage cultures activities. Results showed the thermocline formation at 10 – 14 m depth. DO concentration of 0.32 – 2.25 mg/L at 10 m depth was not suitable for fish survival. Highest chlorophyll a (0.023 mg/L) was recorded at 20 m depth with significant positive correlation with total phosphorus and ammonia. High water level in October 2013 within reservoir may have caused dilution of major nutrients. The cage culture activities at Batang Ai Reservoir had impacted on the water quality at the cage culture sites. Hence, proper site selection should be determined, moderate carrying capacity for cage culture should be considered, extensive feeding during drought should be controlled in order to reduce the impact of cage culture on the water quality of Batang Ai Reservoir.